Bimbingan Kelompok dengan Pengajaran Formula ABCDE Pendekatan Rasional Emotif Behavior untuk Meningkatkan Self Efficacy Mahasiswa Calon Guru - Setiani, Ismarini Bekti; Taufiq, Agus; Suherman, Suherman (Jurnal Kajian Bimbingan dan Konseling, 2017)
The aim of this research is to formulate and develop a group guidance intervention design by teaching the ABCDE formula with a rational emotive behavior approach and testing the effectiveness of the intervention design in increasing the self-efficacy of prospective teachers in the Department of Agro-Industrial Technology Education, Indonesian Education University (UPI). The research uses mixed methods with a concurrent embedded strategy (quantitative as the primary method and qualitative as the secondary method). Data analysis techniques use quantitative (primary) and qualitative (secondary) data analysis. The results of the research show that quantitatively, group guidance using the ABCDE formula teaching with a rational emotive behavior approach has not been effective in increasing the self-efficacy of prospective teacher students due to several causal factors. From the qualitative data, it was found that students were aware of the problem, realized that there were irrational beliefs that caused the problem, understood how to overcome it so that students felt increasingly confident in their ability to become teachers. Future researchers are expected to follow up on this research by applying intervention designs to students who have low and medium self-efficacy categories.